2016
DOI: 10.1016/j.virol.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

A 5′-proximal region of the Citrus tristeza virus genome encoding two leader proteases is involved in virus superinfection exclusion

Abstract: Superinfection exclusion (SIE), a phenomenon in which a primary virus infection prevents a secondary infection with the same or closely related virus, has been observed with various viruses. Earlier we demonstrated that SIE by Citrus tristeza virus (CTV) requires viral p33 protein. In this work we show that p33 alone is not sufficient for virus exclusion. To define the additional viral components that are involved in this phenomenon, we engineered a hybrid virus in which a 5'-proximal region in the genome of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 96 publications
0
29
0
Order By: Relevance
“…Taken together, we mapped the effectors of superinfection exclusion encoded by WSMV and TriMV through gain-of-function assays. In contrast, investigations with CTV identified p33 and L1L2 proteinases as determinants of SIE through loss-of-function (49,54). CTV-encoded p33 was found to be a determinant of SIE since CTV lacking the p33 ORF or with heterologous p33 failed to trigger SIE against identical superinfectors (49).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Taken together, we mapped the effectors of superinfection exclusion encoded by WSMV and TriMV through gain-of-function assays. In contrast, investigations with CTV identified p33 and L1L2 proteinases as determinants of SIE through loss-of-function (49,54). CTV-encoded p33 was found to be a determinant of SIE since CTV lacking the p33 ORF or with heterologous p33 failed to trigger SIE against identical superinfectors (49).…”
Section: Discussionmentioning
confidence: 87%
“…CTV-encoded p33 was found to be a determinant of SIE since CTV lacking the p33 ORF or with heterologous p33 failed to trigger SIE against identical superinfectors (49). Additionally, CTV L1L2 from the heterologous T68 strain failed to elicit SIE, thus confirming the requirement of L1L2 for CTV SIE (54). Yet, neither of the CTV proteins was able to effect SIE when expressed heterologously.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Studies using CTV (different from TCV!) found that SIE can be abolished by replacing three virus-encoded proteins, namely the replication-related L1 and L2 proteases, as well as movement-related p33, with their counterparts from a distantly related CTV strain [8, 31]. Similarly, SIE of WNV and HCV was found to be reversed by mutations in a few viral proteins, among them WNV-encoded 2K and NS4A, and HCV-encoded E1, p7, and NS5A [4, 19].…”
Section: Discussionmentioning
confidence: 99%